Effect of Nutrient Management and Rice Establishment Methods on Groundnut (Arachis hypogaea L.) in Rice–Groundnut Cropping System - Samant, T. K.; Garnayak, L. M.; Paikaray, R. K.; Mishra, K. N.; Panda, R. K.; Swain, S. K. (International Journal of Bio-resource and Stress Management, 2021)
The field experiments were conducted at Agronomy Main Research Farm, Odisha University of Agriculture and Technology, Bhubaneswar, Odisha, India during rabi (November–March) seasons of 2019–2020 and 2020–2021 to evaluate direct and residual effect of nutrient management and rice establishment methods on phenology, growing degree days, growth, yield and economics of groundnut in rice–groundnut cropping system. The experiments were laid out in split-plot designwith three replications. Carryover effect of direct seeding rice favourably influenced the succeeding groundnut crop as compared to that grown after transplanting which had superior growth parameters resulting in 25.7% higher pod yield, oil yield (1.24 t ha-1), gross return (Rs. 136612.7 ha-1) and net return (Rs. 63965.0 ha-1). Residual effect of organic management to preceding rice significantly increased growth, yield attributes, growing degree days at physiological maturity and net return, resulted in highest pod yield of 2.48 t ha-1 in groundnut which was at par with that grown after INM in rice, but was on an average, 17.0% higher than inorganic practice in rice. INM to groundnut increased yield parameters and economics of the crop resulting in 19.7 and 39.3% higher pod yields than 100% and 75% soil test based fertiliser, respectively. Hence, INM under direct seeding to kharif rice benefits the succeeding groundnut crop and direct application of 75% STBN (inorganic)+25% STBN (FYM)+0.2 LR+biofertilisers to groundnut proved beneficial for improving phenology, growing degree days, growth, yield and economics of groundnut in rice–groundnut cropping system.